Discrete element method for generating random fibre distributions in micromechanical models of fibre reinforced composite laminates. (1st April 2016) - Ismail, Yaser; Yang, Dongmin; Ye, Jianqiao
Abstract: A new approach is presented for generating random distribution of fibres in the representative volume element (RVE) of fibre reinforced composite laminates. The approach is based on discrete element method (DEM) and experimental data of fibre diameter distribution. It overcomes the jamming limit appeared in previous methods and is capable of generating high volume fractions of fibres with random distributions and any specified inter-fibre distances. Statistical analysis is then carried out on the fibre distributions generated within the RVEs, which show good agreement with experiments in all statistics analysed. The effective elastic properties of the generated RVEs are finally analysed by finite element method, which results show more reasonable agreement with the experimental results than previous methods.